مؤسسة المجلس الإسلامي الأعلى بالجزائر هيئة استشارية بقيم دعوية - حجار، خالد (University Of Eloued جامعة الوادي, 2024)
ان المؤسسات الدعوية الناجحة اليوم؛ لن تكون جديرة بمسؤولياتها نحو المجتمع والأمة؛ إلا إذا كانت دائمة الاستمرار على تطوير نظمها وأساليبها الدعوية، ومواجهة كل التحديات المحلية أو العالمية في تفعيل عملها التربوي والاصلاحي، ولا تتحقق هذه الديمومة إلا ببعدها الجماعي البعيد عن الأحادية والشخصنة وعن القدسية الفردية، لأن هذه المؤسسات تبنى على مشاريع وافكار ولا تبنى على أشخاص وافراد، وخاصة في هذا العصر الذي أصبح العمل المؤسساتي ضرورة ملحة تَتحِد فيها الجهود والطاقات بتشكيلة نوعية تضم خيرة الإطارات والكفاءات. ومن هذه مؤسسات القائمة والكاملة الأركان النشطة وطنيا في تبليغ تعاليم الإسلام؛ مؤسسة المجلس الإسلامي الأعلى بالجزائر، وهي هيئة دستورية استشارية لدى رئيس الجمهورية الجزائرية؛ تعمل على الاجتهاد في اصلاح الأمور التي تعني الجزائريين في حياتهم اليومية بالدرجة الأولى على أكثر من صعيد، ومدى وارتباطها وعلاقتها بالدين الإسلامي، فالمجلس الإسلامي الأعلى هو مؤسسة عامة ذات طابع استشاري في مجال الدين تتمتع بخصوصيات تطمح من خلالها على خدمة المسلمين في نطاقها المحلى، وتتسع خدماتها لخدمة الامة الإسلامية بحسب سياستها وفي حدود إمكاناتها المادية والبشرية، وهذاما سنثيره بالتحليل في هذه الدراسة. Abstract The study aims to shed light on institutions of a service nature. It includes a group of individuals who are specifically structured and subject to certain controls who seek to embody a package of work, according to specific programs, special methods and methods, and organizational standards related to the fields of their activities, in order to reach the achievement of a number of different goals in their various fields, whether educational or Educational or social, or even working to spread and promote ideological ideas that derive from them and may be subject to them. Among these institutions and bodies are: Da’wah or religious institutions that seek to develop the da’wah work that requires activating the best performance, to achieve the best return that is consistent with the perceptions of these qualitative institutions and in accordance with their future aspirations. It was necessary for those in charge of them to strive to bring about a qualitative development of the da’wa work cycle in a way that is compatible with developments and keeps pace with the rapid developments of On the one hand, and the changes taking place on the other hand, to achieve excellence in all operations carried out by the advocacy institution. Today's successful advocacy institutions; It will not be worthy of its responsibilities towards society and the nation; Unless they constantly continue to develop their systems and methods of advocacy, and confront all local or global challenges in activating their educational and reform work, and this sustainability is only achieved by their collective dimension, far from unilateralism, personalization, and individual sanctity, because these institutions are built on projects and ideas and are not built on people and individuals. Especially in this era in which institutional work has become an urgent necessity in which efforts and energies are united in a qualitative group that includes the best frameworks and competencies. Among these institutions are existing and fully-fledged institutions that are active nationally in conveying the teachings of Islam. The Foundation of the Supreme Islamic Council of Algeria, which is a constitutional advisory body to the President of the Republic of Algeria; It works to strive to reform matters that primarily concern Algerians in their daily lives on more than one level, and to the extent, connection and relationship with the Islamic religion. The Supreme Islamic Council is a public institution with a consultative nature in the field of religion and enjoys characteristics through which it aspires to serve Muslims within its local scope, and expands. Its services to serve the Islamic nation according to its policy and within the limits of its material and human capabilities, and this is what we will discuss through analysis in this study.
مداخلة
Keywords: المؤسسة; المجلس الإسلامي; العمل الدعوي; القيم; Enterprise; Islamic Council; Advocacy work; Value